2022
DOI: 10.1177/20503121221079488
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of thromboembolism and thromboprophylaxis in medical patients admitted to specialized hospital in Ethiopia using Padua prediction score

Abstract: Introduction: Venous thromboembolism is a major cause of mortality and morbidity among hospitalized patients and thromboprophylaxis is one of the key strategies to reduce such events. We aimed to assess venous thromboembolism risk using Padua prediction score, thromboprophylaxis practice, and outcomes in hospitalized medical patients at Tibebe Ghion Specialized Hospital, Bahir Dar, Ethiopia. Methods: A cross-sectional study was conducted among 219 patients admitted to Tibebe Ghion Specialized Hospital from 1 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These findings were consistent with a study by Asmamaw et al, which shows that acute infection and/or rheumatologic disorders 76.7% is the most common diagnosis among hospitalized patients. 24 While another study by Ayalew et al showed that acute infection 51.5% and heart or respiratory disease 25.7% are the commonest. 13 Furthermore, this study was conducted through the winter season, and those conditions are prevalent during that period.…”
Section: Discussionmentioning
confidence: 98%
“…These findings were consistent with a study by Asmamaw et al, which shows that acute infection and/or rheumatologic disorders 76.7% is the most common diagnosis among hospitalized patients. 24 While another study by Ayalew et al showed that acute infection 51.5% and heart or respiratory disease 25.7% are the commonest. 13 Furthermore, this study was conducted through the winter season, and those conditions are prevalent during that period.…”
Section: Discussionmentioning
confidence: 98%
“…A decrease in activity, trauma and/or surgery in less than one month, active tumors, chronic kidney disease, and hypertension are all significantly associated with the occurrence of VTE. 8 In Professor Zhai Zhenguo's study on venous thromboembolism in Chinese inpatients (DissolVE-2), it was found that the main risk factors for surgical and internal medicine inpatients were main surgery (52.6%) and acute infection (42.2%), respectively. 9 Andrea J Darzi conducted a systematic evaluation of the prognostic factors for VTE in hospitalized internal medicine patients and found that the factors with moderate levels of evidence for VTE occurrence were: advanced age, elevated D-dimer levels, and a history of VTE; thrombophilia; cancers; critical illness; and infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, this study analyzed the risk factors of thromboembolism in ANCA-associated vasculitis patients, constructed a thrombus risk prediction model and provided a method for the early identification of thrombosis in AAV patients to help clinicians to actively prevent thrombosis in patients with AAV. 27 …”
Section: Discussionmentioning
confidence: 99%